The impact of employee commitment and satisfaction on training effectiveness / Rumaizah Che Md Nor ... [et al.]. - Che Md Nor, Rumaizah; Mohamed Noor, Norlina; Ibrahim, Sueb; Shahril Anwar, Nor Hannah Shahirah; Mohamad Azlan, Muhammad Akmal (Universiti Teknologi MARA Cawangan Sarawak, 2021)
Employee training and development are essential tools for an organization's continuing growth and productivity. Training and development provide benefits to both the individual and organization as a whole that make the cost and time a worthwhile investment. Thus, the success of employee training and development in an organization can only be quantified in a financial term as return on investment (ROI). The main aim of this study was to investigate the impact of employee commitment and satisfaction on training effectiveness. This study utilized quantitative approach in gathering the data. A total of 100 public sector employees participated in this study.